Chronicles Of Dwelling. Practices Of Informal Building And Forced Resettlement In Santa Filomena Neighbourhood (Lisbon) - Giacomo Pozzi (Antropologia, 2017)
The paper analyzes political practices emerged after the implementation of a governmental rehousing programme in an informal settlement sited in the Metropolitan Area of Lisbon (Portugal). The programme was established for demolishing illegal settlements in the area and rehousing their residents in social houses. At a programmatic level the project framed housing informality and social, ethnic, and spatial segregation as “social plagues”. Twenty years after its original formulation, the actual implementation produced complex dynamics of adaptation and resistance acted by the inhabitants, in majority Cape Verdean migrants. Based on an ethnographic research conducted between 2013 and 2014, the paper shows, on one side, the historical and socio-political building process of the Santa Filomena neighbourhood (Amadora); on the other side, it shows the slum clearance dynamics adopted by local institutions. I sustain that these processes proceeded dialectically in the area, on the border between legality and illegality, formality and informality.